2004
DOI: 10.4049/jimmunol.172.4.2092
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of a Human Polyreactive Ig Expressed in Chronic Lymphocytic Leukemia Generates Memory-Type B Cells That Respond to Nonspecific Immune Activation

Abstract: We generated transgenic mice, designated SMI, expressing unmutated H and L chain Ig genes encoding a low-affinity, polyreactive human (h)IgM/κ rheumatoid factor. These animals were compared with control AB29 transgenic mice expressing a hIgM/κ rheumatoid factor specific for human IgG, with no detectable reactivity with mouse proteins. SMI B cells expressed significantly lower levels of surface hIgM/κ than did the B cells of AB29 mice, but still could be induced to proliferate by surface Ig cross-linking in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 72 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…Evidence for this comes from transgenic mice that express the SMI IgM/ antibody. 40 Transgenic expression of the SMI IgM/ induced mouse B cells to differentiate into nonnaive, memory-type B cells that were hyperresponsive to nonspecific T-cell help. SMI mice, but not control mice that express a human Ig in the absence of specific antigen, had increased numbers of human Ig transgene-expressing B1 and marginal zone (MZ) B cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for this comes from transgenic mice that express the SMI IgM/ antibody. 40 Transgenic expression of the SMI IgM/ induced mouse B cells to differentiate into nonnaive, memory-type B cells that were hyperresponsive to nonspecific T-cell help. SMI mice, but not control mice that express a human Ig in the absence of specific antigen, had increased numbers of human Ig transgene-expressing B1 and marginal zone (MZ) B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the B cells expressing the SMI IgM/ transgenes expressed relatively low levels of surface human Ig, these transgene-expressing B cells still could be selectively deleted in vivo by treatment with mAbs specific for the CRI of the SMI IgM/. 40 Conceivably, anti-idiotypic mAbs could be used during early pathogenesis to target cells that express CRI of Ig associated with an increased risk for neoplastic transformation. In addition, vaccine strategies also could be developed to induce cellular immune responses against peptide epitopes of common motifs found within the CDR3 of Ig frequently expressed in CLL.…”
mentioning
confidence: 99%
“…[72][73][74][75][76] A recent study on transgenic expression of a human IgM polyreactive rheumatoid factor from a patient with CLL demonstrated that expression of polyreactive autoantibodies can allow for development of B cells that are neither deleted nor rendered anergic but have a phenotype of antigen-experienced B cells that respond to nonspecific activation. 77 The similarity between B cells producing natural autoantibodies and CLL B cells could mean that the process of positive selection of natural autoreactive B cells may carry a risk for malignant transformation. 77,78 The results of the present study emphasize the close relationship between autoreactivity and CLL with similarities both in IGKV/IGLV repertoire and CDR3 formation, alluding to a different pathway of B-cell activation, not involving a classical germinal center (GC) reaction response to T-independent antigens.…”
Section: Org Frommentioning
confidence: 99%
“…Furthermore, CLL cells frequently produce "natural" or polyreactive IgM autoantibodies (32)(33)(34)(35)(36)(37). Altogether, the similarity between B cells producing natural autoantibodies and CLL malignant B cells could mean that the process of positive selection of natural autoreactive B cells may carry a risk for malignant transformation (38).…”
Section: Introductionmentioning
confidence: 99%